Syntactic Analysis on Sentence Patterns in Agnez Mo’s Song Lyrics - Marta Izona Ellen Dachi (Institut Agama Islam Negeri Palopo, 2022)
Analyzing sentence patterns turns into more essential in song lyrics as there are regularly misinterpretation of words when they are arranged into sentences in song lyrics. This research was aimed to analyze the types of phrase, clause and describe the sentence patterns in Agnez Mo’s song lyrics through tree diagram. This research employed qualitative research. The data of this research is the four lyrics of Agnez Mo’s songs, they are: Long as I get paid, Coke bottle, Damn I love you and Overdose. In analyzing the data, the research used theory of Miles and Huberman; data reduction, data display and conclusion drawing/verification. The result of the research shows that found types of phrase, clause and sentence patterns. In phrase, there are five types; noun phrase, verb phrase, adjective phrase, adverb phrase and preposition phrase that found in Agnez Mo’s song lyrics. In clause found there are two types; independent clause and dependent clause, which is in the dependent clause also found of each kinds; noun clause, adverb clause and adjective clause in Agnez Mo’s song lyrics. Moreover, there are twenty nine sentence patterns that used in Agnez Mo’s song lyrics. The researcher concludes that there are types of phrases, clauses and sentence patterns which should be known in the syntax. Hence, the researcher hopes that the reader or learner can get knowledge from this research.